Faktor Psikologis Ibu Yang Mempengaruhi Post Partum Blues - Nurul Huda; Sri Dewi Haryati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Childbirth is a natural process experienced by every women. The mother’s various reactions after giving birth will influence attitudes, behavior and emotional levels. Psychological pressure after childbirth is an emotional symptom and feeling where a person feels gloomy, cannot sleep, is excessively physically tired, and does not know what he can do in his new role. However, this is not the case for some women who actually feel sad, irritated, tired, want to be angry, feel meaningless, and hopeless in theirearly days as a mother. If this is allowed to happen, it will certainly have bad consequences for the mother and the baby. These signs and symptoms consititute a condition called postpartum depression (Elvira, 2011). Te aim of this research is to determine the influence of maternal psychological factors on post partum blues. This types of research is quantitative research. The population is all postpartum mothers on the second day after giving birth in the Harapan Bunda delivery room. The sampling technique used was total sampling, namely 45 respondents and analyzed using the Chi Square Test. Based on the the result of research on 45 respondents who were hospitalized, the incidence of post partum blues was found, namely 15 people experienced post partum blues, and 30 people did not experience post partum blues.